The Relevance of Akhlak Material in Building Religious Values and Character Among Sixth-Grade Students at SD Negeri 04 Talaok Bayang Pesisir Selatan - Darwis N, Darwis N (Program Pascasarjana UMSB, 2025)
The global challenge of moral decline among youth, exacerbated by rapid technological advancements and shifting societal values, underscores the urgent need for effective moral education. This issue is particularly critical in Islamic education, where instilling religious values and character (akhlak) is essential for nurturing ethical individuals. This study addresses this global problem by examining the implementation of akhlak education at SD Negeri 04 Talaok, a rural elementary school in Indonesia, aiming to understand its role in building religious values and character among sixth-grade students. The research employs a qualitative case study design, utilizing interviews, observations, and document analysis to explore how akhlak material is integrated into the curriculum and its impact on students' moral and spiritual development. Findings reveal that structured religious activities, curriculum integration, and parental involvement significantly enhance students' discipline, ethical behavior, and spiritual awareness. However, challenges such as behavioral issues, external influences, and limited resources hinder optimal outcomes. The study concludes that akhlak education, when effectively implemented, fosters holistic development, aligning students' academic and moral growth. Despite its contributions, the research is limited by its focus on a single school, suggesting the need for broader studies across diverse contexts. This study highlights the transformative potential of moral education in addressing global moral challenges, offering actionable insights for educators and policymakers in Islamic education.